1998
DOI: 10.3109/15419069809069761
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cell Adhesion Molecules and Cytokines in Murine Antigen-Induced Arthritis

Abstract: Adhesion molecules and cytokines are important in chronic inflammatory conditions such as rheumatoid arthritis (RA) by virtue of their role in cell activation and emigration. Using immunohistochemical techniques we studied the expression of adhesion molecules and cytokines in cryopreserved sections of murine knee joint in the course of antigeninduced arthritis, a n animal model of human RA. Various adhesion molecules and cytokines are expressed in the arthritic joint tissue. LFA-I, Mac-1, CD44, ICAM-I and P-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
(31 reference statements)
6
19
0
Order By: Relevance
“…This response can be blocked with anti-LFA-1 Ab demonstrating that SEB-induced IL-2 production is LFA-1 dependent. 50 values generated from the inhibition of IL-2 mRNA are similar to those obtained in the MLR assay (see Table I). …”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…This response can be blocked with anti-LFA-1 Ab demonstrating that SEB-induced IL-2 production is LFA-1 dependent. 50 values generated from the inhibition of IL-2 mRNA are similar to those obtained in the MLR assay (see Table I). …”
Section: Resultssupporting
confidence: 63%
“…For example, T cells removed from the synovial fluid of RA patients express LFA-1 in a high avidity state on their cell surface, prompting the authors to suggest that synovial environment promotes and/or maintains T cells in an activated state (49). Likewise, LFA-1 and ICAM-1 expression is significantly increased in the pannus, the synovial lining layer, and the synovial infiltrate in murine Ag-induced arthritis (50). In this model, the expression of inflammatory cytokines paralleled that of LFA-1 and ICAM-1.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…28 and 29). In murine AIA, temporal changes in TNF␣, IL-1␤, and IFN␥ expression occur during the acute phase, 1 day after arthritis induction (30,31). We observed that levels of TNF␣ and IL-1␤ expression in synovial tissues were not significantly different between IFN␥ Ϫ/Ϫ and IFN␥ ϩ/ϩ mice at this time; furthermore, titers of antibody to mBSA were comparable (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…As previously described (23), serial cryosections of 5-m thickness from knee joints of IFN-␥ Ϫ/Ϫ mice at the stage of maximum cellular infiltration 1 day after AIA induction were fixed in acetone, blocked with 4% milk/ Tris, and stained with primary 10 g/ml rat mAbs directed against mouse Mac-1 (macrophages and neutrophil granulocytes; Medac), F4/80 (macrophages; Serotec), Gr-1 (neutrophil granulocytes), CD4 (Th cells), or B220 (B cells; all from BD Biosciences) for 1 h at 22°C, followed by incubation with biotinylated secondary goat anti-rat IgG Abs (DakoCytomation) and fixation in 1% formalin. Tris buffer was used for subsequent washing steps.…”
Section: Immunohistochemical Examinationsmentioning
confidence: 99%